ICT Integration in a Multigrade Context: Exploring Primary School Teachers Experiences - Taole, Matshidiso Joyce (Research in Social Sciences and Technology- OpenED Network, 2024)
Technology offers pedagogical affordances that can transform teaching and learning in multigrade classrooms to assist in the process of teaching and learning. However, it is challenging for teachers to effectively integrate technology into their classrooms, given the complex and dynamic multigrade context. The technological pedagogical content knowledge (TPACK) model was a lens through which to explore teachers’ experiences in ICT integration in their multigrade classrooms in selected primary schools in South Africa. A case study design guided this qualitative study. Semi-structured interviews were conducted with twelve teachers thematic analysis was used to analyse data. The findings revealed that access to ICT equipment for teachers and students is crucial. This study has found that generally, it is difficult for teachers to incorporate technology into their teaching because of the caveats, such as the multigrade context and the rural location which presents issues such as lack of basic technology infrastructure, limited training on integrating technology in teaching, time, the teaching context, and support from principals. This study recommends that teachers be trained on ICT usage and given the support needed to function effectively in their multigrade context. For teachers to be digitally connected and ensure ICT integration in the teaching and learning process, they need to be equipped with relevant knowledge and skills to use technology to transform their teaching and create new opportunities for learning.